Cat Scratch Disease: Not a Benign Condition. (3rd October 2018) - Barros, Sandra; de Andrade, Gabriel Costa; Cavalcanti, Cecilia; Nascimento, Heloisa
ABSTRACT: Purpose : Describe a case series of ocular Cat-scratch-disease (CSD) with vision-threatening findings and poor outcomes, indicating severity of disease. Methods : Retrospective case series from the Uveitis Department of São Paulo Federal University from 2011 to 2015. Results : In this period, six eyes of four patients had confirmed diagnosis of CSD. Two were male and two female. Mean age was 24.8 years old [7–45]. Two had bilateral disease. Visual acuity at presentation ranged from no light perception to 20/25. Three patients were treated with doxycycline and one with clarithromycin and prednisone. Visual outcome after treatment ranged from counting fingers to 20/20: 5/6 eyes had final visual acuity of less than 20/40 and 3/6 had final visual acuity equal or less than 20/400. Conclusion : Although usually described as a benign disease with spontaneous resolution, CSD can present with atypical manifestations such as vascular angiomatous lesions, serous retinal detachment, and vascular occlusion syndromes, carrying a severe course and guarded prognosis.